Integrating Audiovisual Media to Enhance Learning Concentration in Early Childhood Settings - Nurmala, Ultsa; Nisa, Khoirun (PIAUD Universitas Islam Negeri Sunan Kudus, 2025)
This study aims to enhance early childhood learning concentration by applying audiovisual media in classroom activities. This research employed a Classroom Action Research (CAR) design, carried out in two cycles, each comprising planning, action, observation, and reflection stages. As a practitioner and researcher, the teacher used a variety of audiovisual tools to improve children’s attention during learning. Data were collected through structured observations and performance assessments that focused on behavioural indicators of concentration, including attentiveness, responsiveness, participation, and task completion. Initial findings revealed that students demonstrated low concentration due to the limited and less engaging use of learning media. To address this issue, diverse audiovisual materials—such as laptops, televisions, sound systems, pop-up cards, posters, and microphones—were systematically integrated into classroom activities. The implementation of these tools resulted in a substantial improvement in students’ concentration, increasing from 58% in Cycle I to 92% in Cycle II. The findings indicate that the structured application of audiovisual media not only enhances focus and engagement but also creates a more interactive and stimulating learning environment in early childhood education settings.